Managing industrial projects a performance oriented approach - DECDFI (My University)
In general, construction progress on pioneer I was satisfactory with the project now approximately 34.7 complete. However, critical path items have continued to fall behind schedule due to difficulty in receiving vendor prints on critical equipment and congested placements for reinforcing bars and structural steel on major buildings.
Keywords: administration; analysis; industrial; automation